Phantasia–The psychological significance of lifelong visual imagery vividness extremes. (September 2020) - Zeman, Adam; Milton, Fraser; Della Sala, Sergio; Dewar, Michaela; Frayling, Timothy; Gaddum, James; Hattersley, Andrew; Heuerman-Williamson, Brittany; Jones, Kealan; MacKisack, Matthew; Winlove, Crawford
Abstract: Visual imagery typically enables us to see absent items in the mind's eye. It plays a role in memory, day-dreaming and creativity. Since coining the terms aphantasia and hyperphantasia to describe the absence and abundance of visual imagery, we have been contacted by many thousands of people with extreme imagery abilities. Questionnaire data from 2000 participants with aphantasia and 200 with hyperphantasia indicate that aphantasia is associated with scientific and mathematical occupations, whereas hyperphantasia is associated with 'creative' professions. Participants with aphantasia report an elevated rate of difficulty with face recognition and autobiographical memory, whereas participants with hyperphantasia report an elevated rate of synaesthesia. Around half those with aphantasia describe an absence of wakeful imagery in all sense modalities, while a majority dream visually. Aphantasia appears to run within families more often than would be expected by chance. Aphantasia and hyperphantasia appear to be widespread but neglected features of human experience with informative psychological associations.